Hubungan Kepemilikan Smartphone dan Uang Saku terhadap Obesitas pada Remaja - Fitri, Samnil Astuti; Rusydi, Riska (Media Gizi Ilmiah Indonesia, 2023)
Technological advances have made lifestyle transformation. On teenagers, using smartphones and the pocket money that can affect of food intake. Based on the World Health Organization in 2018, adolescents in the world who are obese have increased tenfold in the last 40 years. Meanwhile, the prevalence of overweight (5-19 years) in 2016 reached 216 million children. The purpose of the study is to analyze the relationship between smartphone ownership and pocket money on the incidence of obesity in adolescents. This study was carried out at SMP Pembangunan Padang with a research population of class VII and VII students as many as 90 people and as many as 37 people as a research sample.  This study uses a cross-sectional study approach. Samples were taken by random sampling where anthropometric data were processed using the WHO Anthro Plus application and the statistical analysis used was the chi square test with a confidence level of 95% (α = 0.05) and Odds Ratio (OR). The results of the chi square test showed that smartphone ownership was associated with obesity (p-value = 0.03) and OR 4.47, while pocket money was associated with obesity (p-value = 0.00) and OR 2.37. The conclusion of this study is that smartphone ownership and pocket money are associated with the incidence of obesity in adolescents.